2013
DOI: 10.1210/jc.2013-1396
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Tumor Cells in Patients With Adrenocortical Carcinoma: A Monocentric Preliminary Study

Abstract: Our findings provide the first evidence for adrenocortical tumors that CTCs may represent a useful marker to support differential diagnosis between ACC and ACA. The correlation with some clinical parameters suggests a possible relevance of CTC analysis for prognosis and noninvasive monitoring of disease progression and drug response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
2
39
1
Order By: Relevance
“…Additionally, CTC formation was reported to be facilitated by larger tumor size in many solid tumors. [23][24][25][26][27] However, there was no significant correlation between tumor size and CTC count in our results ( Figure 2D; Table 1). …”
Section: Association Of Ctc Number With Ladc Metastasis Statuscontrasting
confidence: 60%
See 1 more Smart Citation
“…Additionally, CTC formation was reported to be facilitated by larger tumor size in many solid tumors. [23][24][25][26][27] However, there was no significant correlation between tumor size and CTC count in our results ( Figure 2D; Table 1). …”
Section: Association Of Ctc Number With Ladc Metastasis Statuscontrasting
confidence: 60%
“…12,15,25 MMP7 and MMP9 were closely linked to tumor dissemination and poor clinical outcomes in NSCLC, breast, pancreatic, adrenocortical, and renal cancers. [23][24][25][26][27] Here, we showed that upregulated expression of MMP7/9 predicts a higher risk of metastasis and a more advanced stage, and we revealed, for the first time, that CTC count is positively correlated with serum levels of MMP7 and MMP9 in LADC. Thus, we speculated whether the ectopic overexpression of MMP7/9 promotes CTCs to shed into the circulation by breaching the continuity of the BM or by digesting the ECM.…”
mentioning
confidence: 60%
“…Conversely, the enrichment by size associated with the positivity for the adrenal-specific marker SF-1 (Fig. 3C) resulted in finding of a significant correlation between the number of CTCs/mL and the tumor diameter or the tumor stage (Pinzani et al 2013), suggesting that CTCs may be a useful marker in aggressive/metastatic ACC. CTCs may be isolated or arranged in groups of 3-20 cells (circulating tumor microemboli, CTMs) which are detached together from the primary lesion.…”
Section: Ctcs: Metastatic Cells Caught In the Act?mentioning
confidence: 97%
“…The presence of CTCs of adrenal origin has recently been characterized in patients affected by ACC compared to benign adenomas (Pinzani et al 2013). These cells are characterized by specific morphological traits, such as nucleocytoplasmic ratio ≥50%, irregular nuclear shape, hyperchromatic nucleus, basophilic cytoplasm and cell size ≥16 µm (Pinzani et al 2013).…”
Section: Ctcs: Metastatic Cells Caught In the Act?mentioning
confidence: 99%
See 1 more Smart Citation